Analisis Kesalahan Berbahasa Teks Berita pada Artikel Kompas Edisi Februari 2024 sebagai Kelayakan Bahan Ajar Membaca Kritis - Akhmar Aribuma; Arina Izzata Amalina; Elis Listiani; Surya Maulana; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Tri Astuti (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research focuses on language error analysis in news texts on online portals. The formulation of the problem in this study is to analyze news writing errors on online portals, one of which is on the February 2024 edition of kompas.com. News can be presented in physical form in the form of newspapers, besides that news can also be presented through online media. Online media or online portals are famous for their speed in spreading information and always updating information that is trending in the community. However, because of this speed, there are often language errors in its presentation. This researebch was carried out to find language errors in the news text on the online portal, be it type process errors, inaccuracies in the preparation process, or inaccuracies in the use of language rules that occur purely from the management or author. Qualitative research is included in the methodology used for this research procedure to produce descriptive data. The technique used in this study is the reading and recording technique. This research uses syntax analysis techniques as data analysis techniques. Based on the analysis that has been done on the news text of the online portal, 2-word omissions, 6-word additions, 3-word subtractions, 10-word formation errors, and 1 punctuation error. In this study, apart from being used to analyze language errors, this research also has the benefit of making online news texts, one of which is the February 2024 edition of the Kompas.com portal to be more easily understood, especially for critical reading teaching materials.